Bibliometric Analysis: Management in Early Childhood Education - Rasto Rasto; Ilham Muhammad; Fadli Agus Triansyah; Swasti Maharani (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Management issues in early childhood education institutions can be a complex challenge for administrators and teaching staff. Therefore, understanding topics of interest and expanding shared networks are necessary to advance development research toward a unified effort. In this bibliometric study, our aim was to disseminate global research trends in the field of Early Childhood Education Management based on publication results, co-authorship between authors and country affiliations, and co-occurrence of author keywords. Using the Scopus database, a total of 181 journal articles were taken which were published between 2013 – 2023. The research results show that since 2016, the number of publications has continued to increase so that the accumulated number of articles published to date continues to increase. About 20% of total global publications are contributed by researchers from the United States, leading 30 other countries/regions. The dominant keywords are PAUD and teacher training. Research trends in early childhood education management over the last 10 years show a focus on initial teacher development and training, as well as improving the quality of education through classroom management, professional development, and human resource management.